Preface to Volume 5, Issue 1 (TEST Trento Student Law Review, 2023)
Dear readers,it is my pleasure to introduce you to the latest issue of the Trento Student Law Review. Yet again, the articles we host provide fresh insights and perspectives on current legal issues, which are of great importance not only to the academic community but also to practitioners.Overall, this volume covers a range of topics relevant to contemporary legal issues, including constitutional populism, online content moderation, tax ruling cases, and land use rights in China. Each article contributes to a deeper understanding of the complex legal landscape in a globalized world.The first essay, titled Criminal and Constitutional Populism Under the Aristotelian Framework by Giacomo Cotti, examines the modern phenomenon of constitutional populism using Aristotle's theory of justice. Cotti argues that Aristotle's account of justice cannot be separated from politics and virtues, and that this framework is particularly useful for assessing the perceived deviant constitution of democracy. Through an assessment of the fields of constitutional and criminal law, Cotti demonstrates how Aristotle's theories can provide valuable insights into the modern phenomenon of constitutional populism.Next, we have Content Moderation: How the EU and the U.S. Approach Striking a Balance between Protecting Free Speech and Protecting Public Interest by Rrita Rexhepi, which explores the issue of content moderation, which is becoming increasingly relevant in the era of politicization and social media. Rexhepi examines how content sharing is regulated in both the EU and the U.S., identifying the benefits and shortcomings of both approaches. While both regions have taken steps to regulate online content, significant differences exist in their approaches. Rexhepi recommends potential solutions to the difficulties that both regions face in regulating online content, including regulating platform transparency, increasing accountability, and establishing oversight bodies.The third article, Recovery of Fiscal State Aid in Tax Ruling Cases and Principles of Legitimate Expectations and Legal Certainty by Amil Jafarguliyev, discusses the application of legitimate expectations and legal certainty principles against recovery orders in tax ruling cases. Jafarguliyev examines how these principles should be applied when dealing with novel and unpredictable interpretations of European Union State Aid rules, using examples from the Apple, Fiat, and Starbucks tax ruling cases. The article argues that legitimate expectations and legal certainty principles should not be applied in a restrictive way when considering the recovery of fiscal state aid.Last but not least, we have The Right to use Land in China: an Instrument of Economic Development? by Camilla Mantese, an article that provides an in-depth review of land use rights in China. The article compares the similarities and differences between land use rights in China and in the Western World, with a specific focus on Italy. Mantese discusses how the land use system evolved historically and analyzes the role of land leasing and land conversion. The article also explores the role of the courts in balancing socialist ideals and capitalistic needs through some decisions on different aspects of the right to use land.The Editorial board would like to express its gratitude to the authors who have contributed their scholarship to this volume: we hope that these articles will encourage further discussion and research in the field of law and that they will provide valuable insights to practitioners and academics.The Trento Student Law Review is also grateful to our University of Trento, the Scientific Publications Office, TESeO - Trento Editions Service for Open science and our Trento Law School for their enduring support, which made the publication of this volume possible.In conclusion, I would like to thank Vice Editor-in-Chief Emma Castellin, the entire editorial team, visiting editors, and collaborators for their commitment and hard work in producing this issue. Thanks to your dedication and passion, the Trento Student Law Review continues to be a source of innovative and high-quality legal research.Faithfully yours,Matteo Maurizi EnriciEditor-in-Chief